2009
DOI: 10.4076/1757-1626-2-7261
|View full text |Cite
|
Sign up to set email alerts
|

An isolated proximal tibiofibular joint dislocation in a young male playing soccer: a case report

Abstract: Isolated dislocation of the proximal tibiofibular joint is a rare injury. We present a 23-year-old caucasian man who sustained a traumatic anterolateral dislocation of the proximal tibiofibular joint. There is no consenus on definitive management, and we review the different published treatment and rehabilitation regimens for this injury. Our patient was successfully treated by open reduction and temporary Kirschner-wire fixation. The authors recommend their structured rehabilitation process involved using cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 12 publications
0
31
0
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12] Although a number of case reports exist describing traumatic proximal tibiofibular dislocation (PTFD) in association with extremity trauma, 2,6,7,9 there are no series examining PTFD because it relates to high-energy traumatic injuries to the lower extremity apart from 1 report in the French literature by Garion et al 8 describing 9 cases. Currently, the majority of the literature focuses on sports-related injury to the proximal tibiofibular joint with the largest series published by Ogden in 1974.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Although a number of case reports exist describing traumatic proximal tibiofibular dislocation (PTFD) in association with extremity trauma, 2,6,7,9 there are no series examining PTFD because it relates to high-energy traumatic injuries to the lower extremity apart from 1 report in the French literature by Garion et al 8 describing 9 cases. Currently, the majority of the literature focuses on sports-related injury to the proximal tibiofibular joint with the largest series published by Ogden in 1974.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Burke et al 9 analysed different regimens of treatment and showed that there was no consensus about definitive management. These authors successfully treated a 23-year-old male patient by open reduction and temporary Kirschner-wire fixation.…”
Section: Discussionmentioning
confidence: 99%
“…These authors successfully treated a 23-year-old male patient by open reduction and temporary Kirschner-wire fixation. Most dislocations can be treated through closed reduction; however, open reduction may be required in some cases due to an anterior muscle tension and/or interposition of disrupted capsular ligaments that may resist reduction 9. MacGiobain et al 8 and Robinson et al 10 also reported a case of open reduction and internal fixation after an initial attempt with closed reduction failed.…”
Section: Discussionmentioning
confidence: 99%
“…The differential diagnosis can be: partial rupture of the ligamentum collaterale laterale (LCL), meniscal cyst or late-ral meniscal tear and distal iliotibial band syndrome 30 . No, or the late diagnosis of the PTFJ dislocation leads to chronic pain in the knee and development of arthrosis PTFJ and because of this it is recommended to compare clinical examination and radiographs with the healthy leg 31 .…”
Section: Disscusionmentioning
confidence: 99%